Unintentionality in Polish Criminal Law - Kowalewska-Łukuć, Magdalena (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
Unintentionality is still a relevant research problem in Polish criminal law. This article is a modest attempt to answer the key questions of unintentionality, i.e. how the volitional and cognitive element is shaped in each form of unintentionality; whether unconscious unintentionality has such elements at all, or whether it is a facade of the subjective side and leads, in fact, to objective responsibility; how to correctly draw the line between conscious and unconscious unintentionality, and what the boundary between unintentionality and intentionality in general looks like.